Influence of Subjective Norms and Risk Perceptions Toward Online Purchase Intentions on E-Commerce - Nasrudin, Inayati; Limakrisna, Nandan; Usman , Bahtiar (International Journal of Management and Business Applied, 2024)
Abstract This research aims to analyze online consumer behavior based on subjective norms and risk perceptions regarding online purchases which are mediated by attitude as an intervening variable in e-commerce applications for the Millennial generation. This research was conducted on the Millennial generation born between the years1981 – 1995 in the Jakarta, Bogor, Bekasi and Tangerang Indonesia. This research design is oriented toward a logic approach that explains a causal relationship and a category of concepts because in this research hypothesis testing of the causal relationship of independent variables and dependent variables is used. This research is a quantitative research by analyzing data based on samples from the population carried out randomly with a chance of error (significance level) 0f 5% and a confidence level of 95%.The forms of research are descriptive survey with a decuctive and quantitave approach. Hypoteses are tested by Structural Equation Modelling (SEM) method. Data analysis uses Structural Equation Modelling(SEM) with a sample consisting of 397. The research results show that Subjective Norms does not directly have a positive effect to Online Purchase Intention nor to Attitude for Using E-Commerce Applications. Subjective Norms indirectly does not have a positive effect on Online Purchase Intention through Attitude in Using E-Commerce Applications. Perceived Risk directly has a negative effect on Online Purchase Intention. Perceived Risk does not directly have a negative effect on the Attitude of Using E-Commerce Applications. Perceived Risk Indirectly does not have a negative effect on Online Purchase Intention through Attitude in Using E-Commerce Applications. Attitude The use of E-Commerce Applications directly has a positive effect on Online Purchase Intention. This research showed that millennials belief that online purchasing intention is not influenced by friends, relatives or colleagues. They tend to shop online because they enjoy as long as the application is easy to use. They also realize that online shopping has some risks but they still shop online as long as the application is safe and has a good reputation.